Low Density Receptor-Related Protein 1 Interactions With the Extracellular Matrix: More Than Meets the Eye - Bres, Ewa E.; Faissner, Andreas (Frontiers in Cell and Developmental Biology, 2019)
The extracellular matrix (ECM) is a biological substrate composed of collagens, proteoglycans and glycoproteins that ensures proper cell migration and adhesion as well as keeps the cell architecture intact. The regulation of the ECM composition is a vital process strictly controlled by, among others, proteases, growth factors and adhesion receptors. As it appears, ECM remodelling is also essential for proper neuronal and glial development and the establishment of adequate synaptic signalling. Hence, disturbances in ECM functioning are often present in neurodegenerative diseases like Alzheimer's disease. Moreover, mutations in ECM molecules are found in some forms of epilepsy and malfunctioning of ECM-related genes and pathways can be seen in, for example, cancer or ischemic injury. Low density lipoprotein receptor-related protein 1 (Lrp1) is a member of the low density lipoprotein receptor family. Lrp1 is involved not only in ligand uptake, receptor mediated endocytosis and lipoprotein transport – functions shared by low density lipoprotein receptor family members, but also regulates cell surface protease activity, controls cellular entry and binding of toxins and viruses, protects against artherosclerosis and acts on many cell signalling pathways. Given the plethora of functions, it is not surprising that Lrp1 also impacts the ECM and is involved in its remodelling. This review focuses on the role of Lrp1 and some of its major ligands on ECM function. Specifically, interactions with two Lrp1 ligands, integrins and tissue plasminogen activator are described in more detail.